Stiffness modulus of Polyethylene Terephthalate modified asphalt mixture: A statistical analysis of the laboratory testing results - Moghaddam, Taher Baghaee; Soltani, Mehrtash; Karim, Mohamed Rehan (Elsevier, 2015)
Stiffness of asphalt mixture is a fundamental design parameter of flexible pavement. According to literature, stiffness value is very susceptible to environmental and loading conditions. In this paper, effects of applied stress and temperature on the stiffness modulus of unmodified and Polyethylene Terephthalate (PET) modified asphalt mixtures were evaluated using Response Surface Methodology (RSM). A quadratic model was successfully fitted to the experimental data. Based on the results achieved in this study, the temperature variation had the highest impact on the mixture's stiffness. Besides, PET content and amount of stress showed to have almost the same effect on the stiffness of mixtures. The optimal amount of PET was found to be 0.41% by weight of aggregate particles to reach the highest stiffness value. (C) 2014 Elsevier Ltd. All rights reserved.